One Piece : Baroque Works Part 8 - Rebellion (Vol 19) Vol. 18, Ace arrives - Oda, Eiichiro, 1975-; Caselman, Lance; JN Productions (San Francisco, CA : Viz Media, 2008)
The Straw Hats at long last reach Alabasta! But their stay is cut short when Luffy attracts too much attention from the Navy. Theyre not the only ones interested in Luffy-- someone from his past has been waiting for him too! Meanwhile, the Baroque Works agents are summoned together when their leader, the dastardly Mr. Zero, aka Sir Crocodile, learns that Luffy is still alive and orders his immediate extermination!
"First published in Japan in 1997 by Shueisha Inc., Tokyo" --Title page verso
"This graphic novel contains material that was originally published in English in Shonen Jump #62-65"--Title page verso
Rated T for teen.
Translated from the Japanese.
Keywords: Pirates; Comic books, strips, etc; Treasure troves; Comic books, strips, etc; Comic books, strips, etc; Japan; Graphic novels; Japan; Pirates; Comic books, strips, etc; Fiction; Treasure troves; Comic books, strips, etc; Fiction; Adventure and adventurers -- Fiction; Graphic novels, Japanese -- Translations into English; Comics (Graphic works); Graphic novels; Action and adventure fiction; Manga; Comics (Graphic works); Action and adventure fiction; Graphic novels; Bandes dessiněs.